Short-term absolute B-cell counts monitoring in systemic sclerosis patients treated with rituximab - L. P. Ananieva; L. A. Garzanova; O. V. Desinova; O. A. Koneva; M. N. Starovoytova; O. B. Ovsyannikova; A. P. Aleksankn; S. I. Glukhova (Научно-практическая ревматология, 2020)
Objective. To evaluate B-cell counts in circulation of SS patients prior to initiation and one year after completion of RTM therapy.Subjects and methods. The study included 71 patients. Median follow up was 13,2±2,0 months (11-18 Mo.). Average cumulative RTM dose during the follow up period was 1,43±0,60 g, with 48 patients receiving < 2 g RTM (Group 1, mean dose 1,1±0,1 g) and 23 patients receiving ≥ 2 g RTM (Group 2, mean dose 2,2±0,6 g). CD19+ lymphocyte counts in peripheral blood were determined using flow cytometry in PSS patients and 20 healthy volunteers matched by sex and age. In SS patients B-cell counts were obtained before initiating RTM, within first month after first administration, then after 6 months and at the end of this study.Results. Baseline absolute and proportional В-lymphocyte counts in peripheral blood was almost similar in SS patients and healthy subjects. Highest counts were observed in SS patients with <3 years disease duration, showing inverse correlation between baseline absolute (R – 0,36, р=0,003) and proportional (R – 0,48, р=0,001) B cell counts and duration of the disease. Complete B-cell depletion from peripheral circulation was documented one month after RTM administration. It persisted in 79% 6 months later, although initiation of B- cell repopulation was documented in some patients. In one year after RTM initiation В-cell counts were significantly lower than at baseline. Complete or partial depletion was still there in the majority of patients with normal counts achieved only in 10% of SS patients. Inverse correlation was found between absolute B-cell count and cumulative RTM dose (R=-0,237, p=0,048).Conclusion. Higher RTM doses resulted in more pronounced В-lymphocytes depletion and more evident improvement of lung function. Current state of practice requires further research to identify most optimal regimens in the context of personalized therapy for SS and other immune-mediated inflammatory diseases.